Analysis and comparison of algorithms for the tomographic reconstruction of curved fibres. Issue 3 (2nd July 2020) - Fröhler, Bernhard; Elberfeld, Tim; Möller, Torsten; Hege, Hans-Christian; De Beenhouwer, Jan; Sijbers, Jan; Kastner, Johann; Heinzl, Christoph
ABSTRACT: We present visual methods for the analysis and comparison of the results of curved fibre reconstruction algorithms, i.e., of algorithms extracting characteristics of curved fibres from X-ray computed tomography scans. In this work, we extend previous methods for the analysis and comparison of results of different fibre reconstruction algorithms or parametrisations to the analysis of curved fibres. We propose fibre dissimilarity measures for such curved fibres and apply these to compare multiple results to a specified reference. We further propose visualisation methods to analyse differences between multiple results quantitatively and qualitatively. In two case studies, we show that the presented methods provide valuable insights for advancing and parametrising fibre reconstruction algorithms, and support in improving their results in characterising curved fibres.